2013
DOI: 10.1536/ihj.54.405
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for the Treatment of Patients With Refractory Takayasu Arteritis

Abstract: SummaryTreatment of refractory Takayasu arteritis (TA) remains an unresolved clinical issue. Patients usually respond to glucocorticoid (GC) therapy, but often relapse on tapering of the GC dose. The aim of the present study was to assess the safety and effi cacy of the interleukin-6 (IL-6) receptor antibody tocilizumab (TCZ) in patients with TA refractory to conventional therapies including GC. Four patients with TA who had shown GC resistance received TCZ infusions (8 mg/ kg) every 4 weeks a total of at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 31 publications
(47 reference statements)
3
38
0
6
Order By: Relevance
“…6 Preliminary studies have reported the efficacy of biological-targeting treatments such as TNF-α antagonists (infliximab, adalimumab, etanercept) and anti-IL-6 receptor (tocilizumab) in TA refractory to other immunosuppressive therapies. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Here, we report the long-term outcome of 49 TA patients treated with TNF-α antagonists and tocilizumab in this French nationwide study, and we compare their safety, their efficacy, and the factors predictive of treatment response.…”
Section: Editorial See P 1685 Clinical Perspective On P 1700mentioning
confidence: 99%
“…6 Preliminary studies have reported the efficacy of biological-targeting treatments such as TNF-α antagonists (infliximab, adalimumab, etanercept) and anti-IL-6 receptor (tocilizumab) in TA refractory to other immunosuppressive therapies. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Here, we report the long-term outcome of 49 TA patients treated with TNF-α antagonists and tocilizumab in this French nationwide study, and we compare their safety, their efficacy, and the factors predictive of treatment response.…”
Section: Editorial See P 1685 Clinical Perspective On P 1700mentioning
confidence: 99%
“…Furthermore, reviews confirmed that tocilizumab may be an effective steroid-sparing option for rapid control of refractory disease activity in patients with Takayasu arteritis. 1,4 Finally, it has been shown that tocilizumab is efficient and well tolerated in patients with refractory Takayasu arteritis 1 ; based on our observation, it may be now an alternative for first-line therapy in selected cases.…”
mentioning
confidence: 65%
“…In patients who remain resistant or intolerant to these agents, biological drugs including tumor necrosis factor inhibitors (infliximab) and tocilizumab are promising. 1 In the presence of a life-threatening arterial stenosis or occlusion, the mainstay of treatment is urgent revascularization of affected organs using surgical bypass, which is associated with lower morbidity-mortality than endovascular intervention. 2 Of note, as a general rule, both endovascular intervention and surgical procedures should be avoided during the active phase of the disease to decrease the risk of vascular complications (eg, restenosis).…”
mentioning
confidence: 99%
“…Overall, further placebo-controlled studies should be conducted to improve the current quality of evidence available for practicing clinicians. Table 1 shows a summary of studies that addressed the use of anti TNF-in patients with TA [17][18][19][20][21].…”
Section: Takayasu Arteritismentioning
confidence: 99%